The femme fatale in "postfeminist" hard-boiled detective fiction : redundant or re-inventing herself? : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in English at Massey University, New Zealand - Redmond, Robert Stanley (Massey University, 2014)
The femme fatale of the hard-boiled era, who arrived in the late 1920s, seduced, shot and poisoned her way through pulp magazines, hard- and paper-backed novels, and films for almost fifty years, as the iconic figure of evil whose abjection secured a new masculine ideal that found its voice in the tough-guy detectives created by the likes of Dashiell Hammett, Raymond Chandler, and Mickey Spillane. But by the 1960s her particular brand of villainy was in decline. In the 1980s a new representation of the dangerous woman, in the form of the tough female detective subverted the genre, by decentring the masculine fantasy that was the source of the femme fatale. The female detectives authored by women, such as Sara Paretsky and Katherine Forrest, were a product of second-wave feminism, which, in the 1960s, agitated for legal and customary rights within the masculine hegemony. By the 1990s, the feminism that had driven a host of social and legal reforms was felt by many to have entered a new phase, allowing for the postulation of the return of the femme fatale within postfeminist detective fiction as the representative of the abject “other.” Contemporary gender politics and new postmodern representational regimes, however, make her return difficult. The cultural meaning attached to her has changed. The question is what different form of marginality, or “otherness,” can take her place? The focus of this study is to answer this question through a study of selected postfeminist detective fiction, framed by the theories of Julia Kristeva and Slavoj Žižek. This research suggests that the initial encroachment of the feminine, in the form of the hardboiled female detective, into the genre, and the further intrusion by aggressive women with no regard for hegemonic law, destabilises the masculine imaginary, and in doing so prepares the ground for a female imaginary, which though framed by the symbolic order, occupies its own space. The fiction of Declan Hughes, Megan Abbott, Stieg Larsson, Ian Rankin, and David Peace provides a mirror into a world where the femme fatale, moves, not necessarily in a linear progression, from being the guarantor of a particular brand of masculine subjectivity to a more diminished stature in the recognition that she is too small a figure for representing evil in a world of global corporations, atomic bombs, and national humiliation. Nevertheless, vestiges of the femme fatale remain in postfeminist crime fiction. However, the demands of feminism and the consequential reshaping of the established order make her survival, in whatever form of “otherness,” tenuous. While statistical evidence may provide some measure of women’s progress, perhaps the detective genre makes a better gauge. It reflects not the job numbers, or percentage of degrees earned, by members of each gender, but the changes wrought upon the sociosymbolic contract, and their effect upon traditional representations of gender, through the destabilising of a once-established masculine ideal.
Keywords: Femme fatale; Femmes fatale in literature; Detective fiction